Kebijakan Pendidikan Islam Masa Orde Lama hingga Orde Baru; Perspektif Sejarah Pendidikan Islam dan Implikasinya pada Pendidikan Islam Era Reformasi di Indonesia - Priarni, Rina; Yaqin, Ainul; Imron, Ali; S.A.P., Rangga Sa’adillah (Sekolah Tinggi Agama Islam Taswirul Afkar Surabaya, 2022)
This research is motivated by the author's personal desire to reveal people's assumptions about changing ministers to change policies, thus making the author to examine how Islamic education policies were implemented in the old order and new order. The author considers it necessary to re-learn about Islamic education policies that were applied during the Old Order and New Order periods in terms of history. The data from this study were taken from various books written by Choirul Mahfud, Marwan Saridjo, Anas Salahudin and books that are relevant to this matter. In this regard, the research used is a qualitative research with the type of library research (library research). While the data collection techniques used are data reduction methods, data presentation, data verification and for data analysis techniques using qualitative descriptive methods and historical analysis.Based on this research, it was found that the analysis of Islamic education policies during the old order of Islamic education was more directed at efforts to renew and multiply Islamic educational institutions that were of higher quality in line with the times. While the analysis of Islamic education policy during the New Order era, the Islamic education policy was almost the same as the socio-political policy, namely the centralization of the depoliticization of society, the control of government power seemed less serious. To analyze the implications of its policies in the old order and new order, Islamic religious education is increasingly gaining an important and strategic position with the policies implemented by the government.